The Unsuspected Allergy - Rawlins, Donna; Smith, Sue; Tyndall, Judi (Operating Room Nurses Association of Canada Journal, 1992)
The unsuspected allergy is a case study of a patient who had an anaphylactic reaction under anaesthesia. This scenario prompted the development of a program that considers potential consumer needs, concerns and ensures patient expectations are identified and met.